Creating Intergenerational Learning Spaces: A collaboration between UNIVEN Community Engagement Programme and Dzomo la Mupo - Netshandama, Vhonani Olive; Nevhudoli, Dolphus (Critical Studies in Teaching and Learning, 2023)
This article is a reflection on a collaborative learning process between a university department and a community-based organisation in creating intergenerational learning platforms. The process entailed the coming together of school learners, university students and community elders in a university setup. Participatory Appreciative Action Learning Research was employed. Purposive sampling was used. Data collection methods approach included were semi-structured interviews, one on one individual interviews and focus group discussions. Three generations, namely school learners, university students, and community elders, participated in selecting the learning areas. These included Indigenous Knowledge Systems (IKS), nature conversation topics, peace-building, manners and Ubuntu, social entrepreneurship, and health issues. The purpose of this initiative was to transfer knowledge, skills, norms, wisdom, and values, among generations, through a collaborative effort between an academic institution and a community. It was hoped that this would provide opportunities for lifelong learning and sharing of knowledge and experience among generations. The collaborative intergenerational learning (IGL) process opened with a series of focused discussions about how to bring to mainstream education (both basic and higher education), platforms for learning that should be inclusive of all forms of knowledges, including indigenous knowledge (IK).